Elevated C-reactive protein level predicts lower gastrointestinal tract bleeding - TOMIZAWA, MINORU (Biomed Rep, 2016)
Lower gastrointestinal (GI) bleeding can be caused by colorectal polyps or cancer. The aim of the present study was to identify blood test variables and medications that can predict lower GI bleeding, which would allow for appropriate colonoscopy. The medical records of patients who underwent colonoscopy from September 2014 to September 2015 were retrospectively analyzed. The selected patients included 278 men (mean age, 67.0±11.5 years) and 249 women (mean age, 69.6±12.0 years). The diagnosis, medications, and blood test variables were compared between patients with and without bleeding. Logistic regression analysis was performed to determine the factors associated with lower GI bleeding. The presence of colorectal polyp and cancer was associated with lower GI bleeding (P=0.0044) with an odds ratio of 6.71 (P=0.0148). No lower GI bleeding was observed in patients taking non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, or anticoagulants. The C-reactive protein (CRP) levels were significantly higher in patients with lower GI bleeding (P=0.0227). The Hb levels were lower in patients with lower GI bleeding, however this finding was not statistically significant (P>0.05). No blood test variable was associated with lower GI bleeding. Elevated CRP was associated with lower GI bleeding, while there was no association between the medications and lower GI bleeding.